De novo donor‐specific antibodies in belatacept‐treated vs cyclosporine‐treated kidney‐transplant recipients: Post hoc analyses of the randomized phase III BENEFIT and BENEFIT‐EXT studies. Issue 7 (2nd April 2018) - Bray, R. A.; Gebel, H. M.; Townsend, R.; Roberts, M. E.; Polinsky, M.; Yang, L.; Meier‐Kriesche, H.‐U.; Larsen, C. P.
Abstract : Donor‐specific antibodies (DSAs) are associated with an increased risk of antibody‐mediated rejection and graft failure. In BENEFIT and BENEFIT‐EXT, kidney‐transplant recipients were randomized to receive belatacept more intense (MI)–based, belatacept less intense (LI)–based, or cyclosporine‐based immunosuppression for up to 7 years (84 months). The presence/absence of HLA‐specific antibodies was determined at baseline, at months 6, 12, 24, 36, 48, 60, and 84, and at the time of clinically suspected episodes of acute rejection, using solid‐phase flow‐cytometry screening. Samples from anti‐HLA‐positive patients were further tested with a single‐antigen bead assay to determine antibody specificities, presence/absence of DSAs, and mean fluorescence intensity (MFI) of any DSAs present. In BENEFIT, de novo DSAs developed in 1.4%, 3.5%, and 12.1% of belatacept MI‐treated, belatacept LI‐treated, and cyclosporine‐treated patients, respectively. The corresponding values in BENEFIT‐EXT were 3.8%, 1.1%, and 11.2%. Per Kaplan‐Meier analysis, de novo DSA incidence was significantly lower in belatacept‐treated vs cyclosporine‐treated patients over 7 years in both studies ( P  < .01). In patients who developed de novo DSAs, belatacept‐based immunosuppression was associated with numerically lower MFI vs cyclosporine‐based immunosuppression. Although derived post hoc, these data suggest that belatacept‐based immunosuppression suppresses de novo DSA development more effectively than cyclosporine‐based immunosuppression. Abstract : At 7 years posttransplant, patients treated with belatacept exhibit a lower incidence of de novo donor‐specific HLA antibody compared to recipients treated with cyclosporine.